Tarawa Fitness Center / Mustaqeem Zolkeflee ... [et al.] - Zolkeflee, Mustaqeem; Ahmad Shapri, Nurul Nadhirah; Shah, Ahmad Fateh; Fuad, Muhammad Mirza Izzat; Jaafar, Norhayati (2021)
Taraw a Fit ness Center is a business entity with five partners in form of partnership business. In this form of business entity, partners carry out the business, share the capital, profits and losses. The business is located at No.36 Jalan Padi Emas ½ ,Uda Business Center , 81200, Bandar Baru Uda, Johor Bahru. We decided to open in that place as that place is like a centre between residential areas and working places. Plus, Uda Business Centre is development business place . Moreover, there are many people workforces at urban and industrial area like Johor Bahru. Tarawa is the newest concept of gym and best route for a healthy lifestyle and fitness for the whole family. We provide you with inspiration, motivation, trainers, equipment, fun and enjoyable fitness environment to keep you sane, healthy and driven them to achieve more goals. Our specialty is we combine fitness and kids in one centre. Tarawa Fitness Center will be open daily through the year. Tarawa Fitness Center will also do the research and development process from time to time in order to fulfil needs and wants of the customer.